Implementation of Mathematics Philosophy In Multicultural Education - Br Ginting, Siti Salamah; Dewi, Izwita; Ahyaningsih, Faiz (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The aim of this research is to explore the implementation of mathematical philosophy in multicultural education. The research method used is the library research method, namely by conducting studies related to multicultural education, philosophy of mathematics, and the implementation of philosophy of mathematics in multicultural education. The research results showed that mathematical philosophy can be implemented in multicultural education, namely in the field of epistemological studies. In the field of epistemological studies, the philosophy of mathematics talks about the origins of the formation of mathematics and the study of knowledge about mathematics. The study of knowledge about mathematics cannot be separated from the characteristics of certainty, truth, objectivity, universalism and rationality. These characteristics can ultimately become the forerunner in the implementation of multicultural education. So as to create multicultural education that upholds justice, equality and unity.